2014
DOI: 10.1007/s00436-014-3999-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of ecto- and endoparasites in domestic cats from Tirana, Albania

Abstract: During 2008 to 2011, faecal samples, ear swabs, and ectoparasites obtained by full body search and total body comb were collected from 252 cats originating from the greater Tirana area. Faecal samples were examined using the McMaster and Baermann techniques, and a subset of 58 samples was tested for Giardia-specific antigen using a coproantigen enzyme-linked immunosorbent assay (ELISA). The ear swabs were examined for the presence of parasitic mites. Overall, almost 93% of the cats were identified harbouring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 51 publications
6
20
0
1
Order By: Relevance
“…Indeed, kittens tend to be more often infected by protozoans (e.g., C. felis and G. lamblia) and ascarids (i.e., T. cati), than adult cats. This trend has been confirmed in studies on T. cati and C. felis, in which it has been shown that infected cats ≤9 months of age are at higher risk for those pathogens (Beugnet et al, 2014;Knaus et al, 2014b). Conversely, in the present study the age of animals was not a risk factor for lungworm infection, since either young or adult animals were infected by A. abstrusus or T. brevior.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, kittens tend to be more often infected by protozoans (e.g., C. felis and G. lamblia) and ascarids (i.e., T. cati), than adult cats. This trend has been confirmed in studies on T. cati and C. felis, in which it has been shown that infected cats ≤9 months of age are at higher risk for those pathogens (Beugnet et al, 2014;Knaus et al, 2014b). Conversely, in the present study the age of animals was not a risk factor for lungworm infection, since either young or adult animals were infected by A. abstrusus or T. brevior.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this controlled study demonstrated that a single topical treatment with Broadline®, at the recommended dose, provided a high level of efficacy against feline Broadline® was shown to be effective against the two major nematodes parasitizing the respiratory system of domestic cats, A. abstrusus and C. aerophila, which are frequently associated as they may share similar paratenic hosts as suggested through co-occurrence in cats (Ng and Kelly 1975;Capári et al 2013;Knaus et al 2014b). A single treatment with Broadline® can reduce burdens of C. aerophila lungworms and markedly reduce or eliminate shedding of eggs.…”
Section: Discussionmentioning
confidence: 94%
“…However, factors like category of cats (e.g., stray, feral, shelter, cattery, well-cared-for pet), habitat (urban or rural), or general access to the outdoors, result in considerable variability in the prevalence of endoparasites (e.g., Borkovcová, 2003;Coati et al, 2003;Omeragić, 2003;Miró et al, 2004;Robben et al, 2004;Romaniuk et al, 2004;Ingstrup, 2008;Gracenea et al, 2009;Keidāns et al, 2009;Overgaauw et al, 2009;Duarte et al, 2010;Ładczuk and Balicka-Ramisz, 2010;Mircean et al, 2010;Traversa et al, 2010;Barutzki and Schaper, 2011;Claerebout et al, 2011;Knaus et al, 2011b;Becker et al, 2012;Mugnaini et al, 2012;Näreaho et al, 2012;Zanzani et al, 2012;Capári et al, 2013;Riggio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%